Sistem Penentuan Penginapan dengan Metode Promethee - Novita Ranti Muntiari; Sunardi Sunardi; Abdul Fadlil (Lembaga Penelitian dan Pendidikan Mandala, 2020)
Every person who travels to a place for a period of days requires lodging with certain criteria and different possibilities for each person. The problem lies in determining the desired lodging recommendations because there are too many choices and various criteria. This study conducted a search for lodging in Yogyakarta with criteria for distance, price, class of lodging, room facilities and supporting facilities. The Promethee method is used to get the rankings of each alternatef by calculating the weights for each criterion. Alternative values desired by visitors are processed to find the value of criteria and preference criteria to then be calculated leaving flow and entering flow to get net flow. This research produces a ranking of data that has been tested using a system with the highest net flow value is 0.5 ie alternative lodging 1 with this is prioritized according to the criteria desired by visitors.